ADOPSI ANAK BERBEDA AGAMA DENGAN ORANG TUA ANGKAT MENURUT FATWA MUI TAHUN 1984 DAN PERATURAN PEMERINTAH NO.54 TAHUN 2007 TENTANG PELAKSANAAN DAN PENGANGKATAN ANAK (STUDI KASUS PADA MASYARAKAT KECAMATAN MEDAN BARU) - Nanda Syavira (Wahdatul Ulum Institute, 2023)
Abstract The aim of this research is to discuss the practice of adopting children of different religions in the Medan Baru sub-district and the procedures for adopting children according to the MUI Fatwa and Government Regulation no. 54 of 2007 concerning the implementation and adoption of children. To answer this problem, the research method used is empirical juridical qualitative with a field problem approach (field research), and supported by researching library materials or secondary data. Materials collected through interviews and observation. Based on the research results, it can be concluded that the regulations for child adoption are contained in the MUI fatwa and government regulation no. 54 of 2007. Adoption of children according to the MUI Fatwa, one of which explains that adoption of children without changing their lineage and religious status, is carried out out of a sense of social responsibility to care for, caring for and educating them with love, like one's own children, is a commendable act and is a pious act recommended by the Islamic religion. During the Jahiliyah era, adoption or better known as tabanni which means taking adopted children was already entrenched. Someone adopts someone else's child to be theirs, and has the same status as their own biological child, then announces it to the public. Meanwhile, according to Government Regulation Number 54 of 2007 Article 1 paragraph 2 concerning the Implementation of Child Adoption, Child Adoption is a legal act that transfers a child from the sphere of authority of parents, legal guardians or other people who are responsible for the care, education and raising of the child into foster parent family environment. There are several reasons for the practice of adopting children of different religions from their adoptive parents in Medan Baru District, namely not having children after a long marriage, with the aim of helping families who are unable to support their children economically. From this research, it can be concluded that the adoption of children of different religions and their adoptive parents came from families who converted to Islam and still had relatives of different religions. The factor of adopting children from different religions is that there is still blood or kinship relations which is the main reason and adoption of children is carried out in a family manner without going to court. The law on the adoption of children of different religions and their guardians is justified in the 1984 MUI Fatwa. Meanwhile, PP No. 54 of 2007, Article 13 is a prohibited legal action.